2008 IEEE International Conference on Control Applications 2008
DOI: 10.1109/cca.2008.4629662
|View full text |Cite
|
Sign up to set email alerts
|

Linearizable feedforward systems: A special class

Abstract: Abstract-We address the problem of linearizability of systems in feedforward form. In a recent paper [22] we completely solved the linearizability for strict feedforward systems. We extend here those results to a special class of feedforward systems. We provide an algorithm, along with explicit transformations, that linearizes the system by change of coordinates when some easily checkable conditions are met. We also re-analyze type II class of linearizable strict feedforward systems provided by Krstic in [9] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We suppose that 6FFnice is linearly controllable and, in particular, (@f j =@x j+1 )(0) 6 = 0 for 1 j n 0 1. We recall briefly the main result of [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We suppose that 6FFnice is linearly controllable and, in particular, (@f j =@x j+1 )(0) 6 = 0 for 1 j n 0 1. We recall briefly the main result of [17].…”
Section: Resultsmentioning
confidence: 99%
“…What made (SFF)-systems appealing is that a stabilizing feedback controller can always be constructed when their linear approximation around the equilibrium is controllable [22], [23]. Problem 1 were tackled in [17] for the feedforward case. If there is a component f j or g j that is nonlinear with respect to the variable xj, then finding an explicit linearizing coordinates becomes extremely difficult and might necessitate solving PDEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is revealed that the family of feedforward systems contains a substantial class that is linearizable by a diffeomorphic coordinate change in [15,16]. An algorithm along with explicit transformations that linearizes a class of feedforward nonlinear systems is in [21]. Sufficient and necessary conditions are given for a control-affine mechanical system that can be transformed into a linear system by a diffeomorphism coordinate change in [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, nonlinear feedforward systems of the form (1.1) under hypothesis (1.2) rarely belong to one of the above classes (an exception is the class of linearizable feedforward systems; see [24,[49][50][51][52]). On the other hand, there are well-established standard control design methodologies that guarantee stabilization of system (1.1) under sampled-data control with zero-order hold [10,22,23,26,27,[41][42][43][44][45] but only in the practical and semiglobal sense.…”
Section: Introductionmentioning
confidence: 99%